Economic benefit and social impact derived by a food loss prevention strategy in the vegetable sector: A spatial and temporal analysis at the regional level - Tonini, Pietro; Odina, Pere Muñoz; Orsini, Francesco; Durany, Xavier Gabarrell (Frontiers in Sustainable Food Systems, 2022)
Introduction Reduction of food loss in the horticultural sector is critical to simultaneously support the transition toward a diet with higher consumption of vegetables and the achievement of policy goals aimed at halving the quantity of wastage by 2030. However, the lack of precise information and the presence of múltiple interconnected factors makes it difficult to assess the potential socioeconòmic benefits and therefore the decision-making process of food loss reduction strategies. Methods A case study approach has been used to assess the econòmic loss and nutrional impact of food loss in the horticulture primary production. The selection of the main vegetable products was based on an historical series while econòmic and nutritional impact were estimated starting from national and European indicator. Results The food loss correspond to 26% of the total production and 14% of the total agricultural production econòmic value. The social analysis confirm the possibility of redistributing food loss among the population even in the most critical months and areas. Discussion The combination of social and econòmic indicator resulted essential to provide key information at the decision-making level to pave the way for the elaboration of short- and long-term food loss reduction strategies. Indeed, no single-bullet strategy can be applied to overcome the problem of food loss as many actor with different needs are involved.